Dissipation of the insecticides pirimiphos-methyl and dichlorvos in stored maize (Zea mays L.) grains = Disipación de los insecticidas pirimifós-metil y diclorvós en granos de maíz (Zea mays L.) almacenados - Strada, Julieta; Bruno, Cecilia; Rojas, Dante Emanuel; Cristos, Diego Sebastian; Nassetta, Mirtha; Balzarini, Mónica; Conles, Martha; Ricca, Alejandra Patricia; Martinez, Maria Jose (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2023)
The aim of this work was to analyze the dissipation dynamics of the insecticides pirimi phos-methyl and dichlorvos in maize (Zea mays L.) grains after post-harvest spray applica tions. The recommendations for their use for Argentina and the Maximum Residue Limits (MRLs) established by local and international pesticide regulations were considered. Supervised experimental trials were conducted in stored maize grains treated with 10 cc.t-1 of pirimiphos-methyl and 20 cc.t-1 of dichlorvos. Samples were monitored 2, 30, 60, 90 and 120 days after application. The pesticides were extracted from the maize grains using the QuEChERS technique and the residues were determined using high-resolution gas chro matography with mass detector. Residue dissipation percentages and daily dissipation rates differed between active ingredients. At 48 hours after application, pirimiphos-methyl residues were 5.1±0.42 μg.g-1, i.e. below the MRLs established by the Argentine Service for Agrifood Health and Quality (10 μg.g-1), the USA (8 μg.g-1) and the Codex Alimentarius (7 μg.g-1), and close to the MRLs established by the EU (5 μg.g-1). Dichlorvos residues reached 2.97±0.27 μg.g-1, and required at least a 90-day withholding period to be lower than the MRLs of the EU.